Nivel de resiliencia en docentes de educación primaria en la Institución Educativa Pública Primaria N° 61015 La Inmaculada, Iquitos 2021 - Ovalle Ruiz, Sara (2022)
The main purpose of this research has been to determine the level of resilience in primary education teachers in the Primary Public Educational Institution No. 61015 La Inmaculada located in the city of Iquitos in the year 2021. The research has been carried out using the type descriptive, with a cross-sectional, field and univariate design as a methodology. Regarding data collection, the survey technique and a questionnaire were considered, which were validated by expert judges on resilience. The research unit has been the primary education teacher and it has been considered as a population and shows 47 of them belonging to the educational institution. The general conclusion is that the level of resilience in primary education teachers in the Primary Public Educational Institution N ° 61015 La Inmaculada is located at 12.8% at the low level, at 66.0% at the medium level and at 21.3% of them on the high level.